Oral Health Status of Children Age 6-12 Years in Rawalpindi, Islamabad Pakistan: Oral Health Status of Children - Farrukh Habib, Muhammad; Khan, Jawaria; Pervaiz, Ayesha; Shaheen, Dur e Yakta; Diba, Farah; Raisani, Sher Afgan; Bashir, Nazia; Noreen, Mehmoona; Habib, Fatima; Yasmin, Rehana (Pakistan Journal of Health Sciences, 2023)
Dental caries seems to be a significant public health issue and a common non-communicable disease. And is more prevalent in age group 6-12 years. There has never been a national oral health survey conducted in Pakistan between age 6-12 years in recent years. The purpose of this study was to look into the dental health of children between the ages of 6 and 12. Objectives: To determine the oral health status of children age 6-12 years using Decayed, Missed, Filled tooth Index. Methods: A cross-sectional study was carried out which included 385 children age between 6-12 years, using a simple random sampling. Children were evaluated in schools, and data collected included details on caries and the condition of the gingiva. The WHO's methodology and standards were used for oral examination. Results: Mean DMFT index of children age 6-12 years came out to be 2.28 ± 0.97. More than 2/3rd of children age between 6-12 years needs urgent dental care. Conclusion: The oral health status of children age between 6-12 years is unsatisfactory and higher DMFT index than expected. To effectively prevent and control burden of dental caries and promote gingival health, the oral health program must be implemented. Dental caries seems to be a significant public health issue and a common non-communicable disease. And is more prevalent in age group 6-12 years. There has never been a national oral health survey conducted in Pakistan between age 6-12 years in recent years. The purpose of this study was to look into the dental health of children between the ages of 6 and 12. Objectives: To determine the oral health status of children age 6-12 years using Decayed, Missed, Filled tooth Index. Methods: A cross-sectional study was carried out which included 385 children age between 6-12 years, using a simple random sampling. Children were evaluated in schools, and data collected included details on caries and the condition of the gingiva. The WHO's methodology and standards were used for oral examination. Results: Mean DMFT index of children age 6-12 years came out to be 2.28 ± 0.97. More than 2/3rd of children age between 6-12 years needs urgent dental care. Conclusion: The oral health status of children age between 6-12 years is unsatisfactory and higher DMFT index than expected. To effectively prevent and control burden of dental caries and promote gingival health, the oral health program must be implemented.